Penggunaan Metode Certainty Factor Pada Sistem Pakar Deteksi Kerusakan Perangkat Keras (Hardware) Komputer di Laboratorium Berbasis Android - Rima Tamara Aldisa (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
The system is designed to assist in providing the final result of knowledge of the damage that occurs in computer hardware in the laboratory, the expert system here imitates or is similar to a laptop service expert in knowing the damage that occurs. This system is built using Android which can be installed by the user, the user here is the laboratory assistant and the main laboratory head, this system helps in dealing with the damage conditions that occur in the computer. From the research conducted, an android-based expert system for diagnosing the end of the situation using the factor certainty method can provide information about 4 types of damage diagnoses, 12 damage symptom data, provide information about the cause to suggestions for final treatment. The results of the test using the Alpha Test on 20 participants who we asked to install the expert system first on the cellphone. The participants consisted of laboratory assistants, laboratory heads, the answer choice was